توزيع العبء المتدرج باستخدام نمط النقل اللاتزامني (Latakia University Journal -Engineering Sciences Series, 2019)
In this paper, a generic load balancing strategy over a preplanned Asynchronous Transfer Mode (ATM) backbone is tested. Distributed systems are subject to an exponential increase in size due to widen use of distributed database banks. The ATM is moving promptly towards being a backbone for WANs. In this study, The ATM Virtual Path (VP) concept is used to plan the underlying distributed system network. ATM can support a guaranteed quality and a fast service. The of ATM characteristics give it the advantage of being a potential response to the transparent nature of remote accessing and load balancing which may require heavy traffic to perform the information policy in distributed systems. Preferred sets are chosen, VPs are established, the system is integrated and numerical results are presented. يهدف هذا البحث إلى دراسة واختبار طرق توزيع العبء في المنظومات الموزعة (Distributed System) باستخدام نمط النقل اللاتزامني (Asynchronous Transfer Mode) كعمود فقري للنظام, من المعروف أن المنظومة الموزعة آخذة بالتوسع الهائل. وذلك بسبب استخدام بنوك قواعد البيانات الموزعة والمتباعدة ومن المعروف أيضا أن ATM هو في طريقه إلى أخذ موقع أساسي في شبكات WAN. في هذه الدراسة تم الأخذ بمفهوم Virtual Path VP لتخطيط البنية التحتية لمنظومة الشبكات الموزعة حيث أن ATM يضمن الخدمة من حيث السرعة والنوعية وهذا ما نحتاجه في عملية توزيع العبء حيث تحتاج هذه العملية إلى تبادل هائل للمعلومات لاتخاذ القراراات الماسبة بأقصى سرعة ممكنة من أجل اتمام هذا لاعمل على شكل منظومة متكاملة  اقترحنا استخدام خوارزمية اختيار المجموعات المفضلة prefered sets وإنشاء المسارات التخيلية VPS اللازمة التي تمكن من الحصول على نتاج محاكاة موثوقة وأخيرا تم عرض النتائج العددية للبحث.